GERAKAN KHURUJ FI SABILILLAH SEBAGAI UPAYA EDUKASI MEMBENTUK KARAKTER MASYARAKAT: STUDI KASUS DAKWAH JAMA’AH TABLIGH TEMBORO MAGETAN MELALUI PENDEKATAN FRAMING - Moh. Yusuf (UIN Sayyid Ali Rahmatullah Tulungagung, 2017)
The existence of the movement khuruj fi sabilillah Jama'ah Tabligh was first present at Temboro, Magetan faced many obstacles. Obstacles not only by the preaching community that existed first but the structure of political opportunity as well providing a challenge that is not trivial. In the end, the da'wah khuruj f sabilillah movement is able to form the character of Temboro Muslim citizens into a typical Islamic-salafi society through educational da'wah khuruj fisabilillah. This study uses framing theory as an analytical tool in reading events, framing experiences into meaning and guiding collective action. Jama'ah Tabligh can cultivate the interest of the people of Temboro to khuruj fi sabilillah with the conception of meaning framed, that khuruj fi sabilillah is manhaj